Anti-inflammatory, analgesic and anti-pyretic activities of standardized root extract of Jasminum sambac - Sengar N.; Joshi A.; Prasad S.K.; Hemalatha S. (My University, 2025)
Ethnopharmacological relevance The plant Jasminum sambac L. (Oleaceae) is cultivated throughout India. The leaves and roots of the plant are used traditionally in the treatment of inflammation, fever and pain. The leaves of the plant have been reported to posses significant anti-inflammatory and analgesic activities.; Objective: To scientifically validate anti-inflammatory, analgesic and anti-pyretic activities of roots from Jasminum sambac.; Materials and methods Ethanol root extract of Jasminum sambac (EJS) was standardized using HPTLC and was subjected to acute oral toxicity study. Further, analgesic activity of EJS at 100, 200 and 400 mg/kg, p.o. was evaluated using writhing test on Swiss albino mice and tail-flick test on Charles Foster albino rats. Anti-inflammatory activity of EJS was assessed by carrageenan-induced rat paw edema, cotton pellet-induced granuloma and Freund's adjuvant-induced arthritis models, while antipyretic activity was evaluated using Brewer's yeast induced pyrexia. In addition, biochemical parameters such as alkaline phosphatase (ALP), aspartate transaminase (AST), alanine transaminase (ALT), lipid peroxidation (LPO), superoxide dismutase (SOD) and catalase (CAT) in blood serum and edematous tissue of rats exposed to acute (carrageenan) and granulomatous tissue in sub-chronic (cotton pellet granuloma) inflammation models were also evaluated.; Results Phytochemical analysis of EJS revealed the presence of flavonoids, phenols, saponins, tannins and carbohydrates in major quantities, while the quantity of hesperidin in EJS (using HPTLC) was found to be 4.25% w/w. EJS at 400 mg/kg, p.o. reduced writhing count up to 49.21%, whereas in tail-flick test, EJS in a dose dependent manner increased latency in flicking tail. EJS at 400 mg/kg, p.o. showed significant anti-inflammatory activity after 2nd, 3rd, 4th and 6th h of treatment in carrageenan-induced edema, while a 33.58% inhibition in cotton pellet induced granuloma formation was observed at same dose level. EJS significantly (p<0.001) inhibited adjuvant-induced arthritis and also showed significant antipyretic activity. Further, a significant reversal in alterations of all the biochemical parameters (except ALP) in tissues was also observed.; Conclusions The study confirms the anti-inflammatory, analgesic and antipyretic activity of EJS which may be attributed to the presence of various phytoconstituents quantified especially hesperidin which have already been reported for its significant role in the treatment of inflammation and associated problems. © 2014 Elsevier Ireland Ltd.